Basic Principles for Elaboration of Technical Requirements to Control and Protective TRB Turbine Systems - N. V. Panteley (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers and provides methodology for calculation of maximum over speeding value of a turbine rotor in the case when we face the failure of all its protective systems. It is presented a derivation of main equations required for making the calculation and the paper also cites results of their practical application at an industrial TRB (Turbine of the Republic of Belarus) turbine while constructing its protective control systems.